2022
DOI: 10.3390/ma16010258
|View full text |Cite
|
Sign up to set email alerts
|

On the Formability of Medium Mn Steel Treated with Varied Thermal Processing Routes

Abstract: In this contribution, we investigate the influence of thermal processing routes on the formability of medium Mn steel by assessing the strain hardening coefficient and anisotropy factor using the uniaxial tensile test. Medium Mn steel processed by intercritical annealing (IA) at 680 °C for 4 h demonstrates better formability than steel treated with a combination of IA at 800 °C for 10 min and quenching and partitioning (Q&P), based on the much higher strain hardening coefficient (n) and comparable anisotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Yi et al [4] have mentioned that the actual trend for developing AHSS that exhibit more than 30% of total elongation is with the purpose to ensure a successful plastic forming and also maintain enough "residual ductility" in the part for a crash event. Recently, Zhang et al [5] reported the effect of different heat treatments on the formability of a Fe-10Mn-0.2C-2Al-0.1V (in wt.%) steel. They concluded that IA produced better formability in terms of strain hardening in comparison with the IA-Q&P treatment, it was associated to an enhanced TRIP effect produced in the first treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Yi et al [4] have mentioned that the actual trend for developing AHSS that exhibit more than 30% of total elongation is with the purpose to ensure a successful plastic forming and also maintain enough "residual ductility" in the part for a crash event. Recently, Zhang et al [5] reported the effect of different heat treatments on the formability of a Fe-10Mn-0.2C-2Al-0.1V (in wt.%) steel. They concluded that IA produced better formability in terms of strain hardening in comparison with the IA-Q&P treatment, it was associated to an enhanced TRIP effect produced in the first treatment.…”
Section: Introductionmentioning
confidence: 99%